The Performances of ESP Lecturers' Pedagogical and Professional Competence in Teaching Speaking Class - Wahyuni, Rahmi Nur Baity; Rozi, Fahrur (English Education Journal, 2020)
Pedagogical and professional competence in the ESP teaching and learning process is important because achieve goals of national education, teachers and lecturers are required to be a professional by having those competences. This research aimed to analyze the lecturers’ pedagogical and professional competence in teaching ESP in speaking class in order to explain and analyze the relation of performanceof it towards ESP learners’ performance in speaking skill. Qualitative case study was employed in order to investigate the performances of pedagogical and professional competences of English lecturers in teaching ESP and how is the relation between those performances towards learners’ speaking performances. The findings showed different performances of pedagogical and professional competence in very good and good categories. Then, there was positive relation between performances of pedagogical and professional competence towards ESP learners’ speaking performances since mean values of ESP learners’ speaking performance passed the minimum score of ESP subject. Practically, the result of this study gave benefit for educators and everyone who get involved and interested in the performance of lecturers’ pedagogical competence to make it as knowledge to develop their knowledge in English education, especially in ESP context.